Effect of Standard Heparin and a Low Molecular Weight Heparin on Thrombolytic and Fibrinolytic Activity of Single-Chain Urokinase Plasminogen Activator In Vitro - Lourenço, D M; Dosne, A M; Kher, A; Samama, M (Thrombosis and Haemostasis, 1989)
The effect of unfractioned heparin (UH) and low molecular weight heparin (LMWH) (Kabi 2165 - Fragmin®) on in vitro scu-PA thrombolytic and fibrinogenolytic activity was investigated. Thrombolytic activity was evaluated by following lysis of radiolabeled plasma clot immersed in plasma in presence of scu-PA alone or with either form of heparin. A 200 IU/ml scu-PA concentration produced clot lysis within 7 hr. UH or LMWH led to a slightly faster clot lysis which was statistically significant only at the 2nd and 3rd hour. No significant difference could be evidenced between UH and LMWH effect. During clot lysis, plasmin, generated within the clot led to a gradual transformation of scu-PA to tcu-PA, specially after a 4-hr incubation. Appearance of tcu-PA activity in the plasma surrounding the clot was significantly inhibited by either form of heparin. This finding contrasts with results observed in purified systems and suggests the presence of heparin-dependent plasma factor(s) inhibiting tcu-PA formation or its activity. Possible candidates might be anti-thrombin III and PAI-3.No fibrinogen breakdown was observed when plasma was incubated for 7 hr at 37° C in presence of scu-PA alone (200 IU/ ml) or with either form of heparin. However, in presence of a plasma clot, an important fibrinogen breakdown was observed during clot lysis reflecting the action of plasmin and/or tcu-PA generated within the clot, in the surrounding plasma. Fibrinogenolysis was less pronounced in the presence of both heparin preparations possibly as a consequence of the reduction in the tcu-PA level. These results underline the importance of plasma factors in the interaction of heparin with plasminogen activators such as scu-PA.
Keywords: scu-PA; Standard heparin; Low molecular weight heparin